Evaluation of gas diffusion electrodes as detectors in amperometric hydrogen sensors - Lizcano-Valbuena, William Hernando; Perez, Joelma; Paganin, Valdecir Antonio; Gonzalez, Eva Ruth (Eclética Química, 2005)
This work is directed to the study and evaluation of gas diffusion electrodes as detectors in hydrogen sensors. Electrochemical experiments were carried out with rotating disk electrodes with a thin porous coating of the catalyst as a previous step to select useful parameters for the sensor. An experimental arrangement made in the laboratory that simulates the sensor was found appropriate to detect volumetric hydrogen percentages above 0.25% in mixtures H 2 :N 2 . The system shows a linear response for volumetric percentages of hydrogen between 0.25 and 2 %.